2001
DOI: 10.1023/a:1016602329047
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Trace metal concentrations in phytoplankton were determined in seven locations (Stations I-VII) of the Kuwait Coast, known for significant industrial and recreational activities. Trace metal concentrations in phytoplankton (20-200 microns size) occurred in the sequence of Zn > Pb > Cu > Ni at Stations I-III and VII, and Zn > Cu > Ni > Pb at Stations IV-VI. Station III showed higher concentrations of all the analyzed metals than at other stations. Toxicity tests to phytoplankton revealed a significant decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Again, selecting commonly tested metals (Zn, Cu, Cd and Fe), LOEC and LC 50 data were generated for P. waltoni along with tissue specific Bioaccumulation Factors (BAFs). Field collected phytoplankton have also been used to assess differences in response to metal toxicity (Cu, Ni, Pb, Zn), along with the inter-site variability in metal accumulation (Bu-Olayan et al, 2001). Studies have also found site of collection to influence the sensitivity of intertidal invertebrate species, blue crab Portunus pleagicus and the cockle Tapes sulcarius to Hg when subject to short-term laboratory based 96 h toxicity tests (Bu-Olayan and Thomas, 2015).…”
Section: Toxicological Studiesmentioning
confidence: 99%
“…Again, selecting commonly tested metals (Zn, Cu, Cd and Fe), LOEC and LC 50 data were generated for P. waltoni along with tissue specific Bioaccumulation Factors (BAFs). Field collected phytoplankton have also been used to assess differences in response to metal toxicity (Cu, Ni, Pb, Zn), along with the inter-site variability in metal accumulation (Bu-Olayan et al, 2001). Studies have also found site of collection to influence the sensitivity of intertidal invertebrate species, blue crab Portunus pleagicus and the cockle Tapes sulcarius to Hg when subject to short-term laboratory based 96 h toxicity tests (Bu-Olayan and Thomas, 2015).…”
Section: Toxicological Studiesmentioning
confidence: 99%